2017
DOI: 10.1111/1744-9987.12563
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of Hepatocellular Carcinoma in Japanese Patients Undergoing Dialysis

Abstract: Patients with end-stage renal disease who are undergoing dialysis may be at high risk of developing hepatocellular carcinoma (HCC). We investigated the characteristics and prognosis of HCC in patients undergoing dialysis in Japan. Patients characteristics, progression of HCC at diagnosis, and survival rates after diagnosis were compared between 108 HCC patients undergoing dialysis and 526 non-dialysis patients followed up at liver center. The comparisons were also performed after adjusting for patient age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
12
1
Order By: Relevance
“…We also evaluated the prognostic determinants in solely dialysis patients with HCC and found that larger TTV, ascites, duration of dialysis ≤24 months, diabetes-related cause of dialysis, and non-curative treatments were associated with decreased long-term survival. These results were largely consistent with previous studies (24)(25)(26). Notably, those with shorter duration of dialysis were associated with poor outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also evaluated the prognostic determinants in solely dialysis patients with HCC and found that larger TTV, ascites, duration of dialysis ≤24 months, diabetes-related cause of dialysis, and non-curative treatments were associated with decreased long-term survival. These results were largely consistent with previous studies (24)(25)(26). Notably, those with shorter duration of dialysis were associated with poor outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported comparable survival rates between dialysis and non-dialysis patients with HCC (5,24). By contrast, another study from Japan revealed that patients receiving dialysis had lower survival rate compared with non-dialysis patients (25). Therefore, the prognosis of HCC patients with dialysis was highly debated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only a small proportion (3.6%) of RI patients received dialysis. Consistently, we found that patients without dialysis survived longer than patients with dialysis [36]. However, the impact of dialysis requires further large-scale studies to confirm.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, patients on haemodialysis are frequently not screened for HCC, even if a considerable percentage of them, especially those who are HCV positive, are at risk of HCC. 119 Therefore, a collaborative effort among HCC and CKD specialists is crucial to improve patient outcomes ( Table 2).…”
Section: Patients Undergoing Haemodialysismentioning
confidence: 99%